An Analysis of Research Backgrounds of EFL Students' Research Proposal - Rahmawansyah bin Sahib; Andi Miftahul maulidil Mursyid (English Department - University of Sultan Ageng Tirtayasa, 2020)
This research analyzed research backgrounds, namely research territory (claim centrality, problems, a review literature) and research niche (gaps) of EFL students' research proposals. The research design was qualitative research employing text analysis. The researchers used a random sampling technique to select two research proposals' backgrounds. Moreover, the contents of the research proposals' backgrounds analyzed using the CARS model (Swales & Feak, 2012). The research findings showed that the students tend to find it difficult in addressing the research territory (problems) and establishing a niche (gap). First, the students apparently find it difficult to develop their ideas as a result of the students apparently find it difficult to establish a niche (gaps). Second, the students tend to find it difficult to compose their ideas started from the general views to the specific thoughts. Last, the students lack consistency in using tenses.